UPAYA MEMBANGUN HARMONISASI MASYARAKAT MELALUI BUDAYA SUNGAI DI KOTA BANJARMASIN : Studi Fenomenologi Pada Masyarakat Bantaran Sungai Martapura, Kota Banjarmasin Kalimantan Selatan - Marini, - (2019)
ABSTRACT Marini (1707544). Efforts to Build Community Harmonization Through River Culture in Banjarmasin City. (Phenomenology Study in the Society of the Martapura River, Banjarmasin City, South Kalimantan). Traders in floating markets seem to make the river a place where they find the meaning of life. The growing collaboration of all parties through populist economy and the activities of traders in the floating market in the formation of Civic Responsibility in the Banjarmasin community. So that it can give birth to harmonization of society. The research conducted aims to obtain an overview of the role of the community, local government and community leaders in building community harmonization in Banjarmasin City. This study uses a qualitative approach through phenomenological study methods. Data collection is done through interview techniques, observation, documentation, and literature studies. The results of this study found the following: (1) The role of citizens in building community harmonization in the city of Banjarmasin was marked by the existence of floating markets as a social institution for Banjarmasin people, especially those living on the banks of the river having the influence of customs and river culture as well as the people's economy ; The role of community leaders in building harmonization of society with kinship (rakat); The role of the local government in building harmonization of society is to encourage the existence of a floating market as a value-laden ecotourism through river culture in the city of Banjarmasin. (2) Way of inheritance in building harmonization of society from the older generation to the younger generation through river culture, namely floating markets, one of the hereditary traditions of the Banjar people as a form of adaptation of the people living on the banks of the river. (3) Inhibiting factors in the development of harmonization of society from the older generation to the older generation through the culture of the river where in the current era of modernization by extracting noble values that can still be seen from the behavior of Banjarmasin people, one of them is through the preservation of floating markets in Banjarmasin. with the collaboration of various stakeholders ranging from floating market traders, the local community itself, academics and local government. Keywords: Harmonization, River Culture through Social Culture, Democratic Economy, and Civic Responsibility.